2012
DOI: 10.1371/journal.ppat.1002571
|View full text |Cite
|
Sign up to set email alerts
|

A Peptidoglycan Fragment Triggers β-lactam Resistance in Bacillus licheniformis

Abstract: To resist to β-lactam antibiotics Eubacteria either constitutively synthesize a β-lactamase or a low affinity penicillin-binding protein target, or induce its synthesis in response to the presence of antibiotic outside the cell. In Bacillus licheniformis and Staphylococcus aureus , a membrane-bound penicillin receptor (BlaR/MecR) detects the presence of β-lactam and launches a cytoplasmic signal leading to the inactivation of BlaI/MecI repressor, and the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…In addition, peptidoglycan fragments are found to be involved in the regulation of ␤-lactamase expression in Gram-positive bacteria, although the regulatory mechanism is quite different from that of AmpC (17). These observations suggest that the involvement of peptidoglycan recycling is a generic mechanism in ␤-lactamase expression.…”
mentioning
confidence: 95%
“…In addition, peptidoglycan fragments are found to be involved in the regulation of ␤-lactamase expression in Gram-positive bacteria, although the regulatory mechanism is quite different from that of AmpC (17). These observations suggest that the involvement of peptidoglycan recycling is a generic mechanism in ␤-lactamase expression.…”
mentioning
confidence: 95%
“…This cleavage would render the dimeric repressor inactive and release it from its DNA-binding site. A similar effect of inhibitor inactivation, which was not based, however, on a proteolytic pathway but on the intracellular presence of a short dipeptidic peptidoglycan fragment induced by BLA stress, has been recently described for B. licheniformis (28). Finally, release of transcriptional repression would elicit biosynthesis of MecA/BlaZ.…”
mentioning
confidence: 55%
“…This cleavage event is believed to be initiated by the b-lactam acylation of BlaRs, resulting in conformational changes in the transmembrane bundle that carry the signal across the bilayer (Zhang et al 2001). Although the ultimate result of BlaRp activation is the cleavage of BlaI, it is not yet certain whether BlaI is the direct substrate of BlaRp or the end result of a proteolytic relay (Llarrull and Mobashery 2012;Amoroso et al 2012).…”
Section: Sensor-/transducer-mediated Regulation Of B-lactam Resistancementioning
confidence: 99%
“…These peptides and their breakdown products are postulated to be transported to the cytoplasm via conserved ABC transporters or the phosphotransferase system for recycling (Reith and Mayer 2011). Recently, it has been demonstrated that in B. Licheniformis, a cell-wall-derived dipeptide fragment, g-D-Glu-m-DAP, is capable of binding the BlaI (MecI) repressor, leading to its dissociation from the bla operon and subsequent induction of the b-lactamase, BlaP (Amoroso et al 2012). Although the exact pathway for the generation of the dipeptide has not yet been discerned, this finding draws an interesting parallel between recycling and antibiotic resistance in Gram-positive and Gram-negative bacteria.…”
Section: Pg Recycling and Regulation Of B-lactam Resistancementioning
confidence: 99%